Motorized winter recreation impacts on snowpack properties - Heath, Jared Tucker, author; Fassnacht, Steven, advisor; Elder, Kelly, committee member; Stednick, John, committee member; Wilson, Kenneth, committee member (Colorado State University. Libraries, 2011)
Winter recreation, consisting of snowshoeing, skiing, snowboarding, and snowmobiling, has been increasing annually in Colorado's forests. This increase in recreational activity creates direct and indirect wildlife interactions. Motorized winter recreation in the backcountry compacts the snow possibly influencing the physical and mechanical properties of the snowpack. Snow depth, density, stratigraphy and grain characteristics control to the insulating properties of the snowpack and create habitat for small non-hibernating mammals. Changes to these physical properties and compaction of the subnivean space may be detrimental to these species. Two hypotheses were formulated: (1) a snowpack compacted by motorized winter recreation will result in changes to physical and mechanical properties of the snowpack; and (2) the amount of motorized winter recreation and the depth of snow when motorized winter recreation begins affects the physical properties of the snowpack. During the 2009-2010 winter season snow compaction plots near Rabbit Ears Pass and Fraser Experimental Forest, Colorado were manipulated with varying use of motorized winter recreation (low, medium and heavy use) beginning on different snow depths, shallow (30 cm) and deep (120 cm). Physical and mechanical properties of the snowpack, including snow density, temperature, snow depth, snow water equivalent, stratigraphy, hardness and ram resistance were measured and used to examine the statistical difference between no use and varying degrees of motorized winter recreation (low, medium and heavy use). The results were used to infer implications on changes to the insulative value of the subnivean space and the potential for movement by subnivean mammals. The largest differences in snowpack properties were associated with motorized winter recreation beginning on a shallow snowpack. Compaction from motorized winter recreation that began on a shallow snowpack increased both mean and subnivean density, hardness, and ram resistance, which resulted in significant differences (p<0.10) between varying use of motorized winter recreation and no use. Snow depth and basal temperatures (ground/snow interface) decreased as a result of motorized winter recreation beginning on a shallow snowpack (p<0.10), while temperature gradients were unaffected throughout the duration of the winter season. Implications to changes in these snowpack properties could decrease the insulative value of the snowpack and make movement by small mammals that utilize the subnivean space more difficult. On the contrary, motorized winter recreation that began on a deep snowpack showed no significant difference suggesting later initiation of use minimizes changes to snowpack properties from compaction.
Keywords: motorized winter recreation; snowpack properties; snowmobiles; Colorado; compaction; subnivean space